Reliability and validation of the Korean Compassionate Communication Scale - Jo Hae-Kyung; Park Sook Kyoung; Song EunJu (Sciendo, 2019)
The aims of this study were to develop the Korean Compassionate Communication Scale and to test its validity and reliability.